42nd AIAA Aerospace Sciences Meeting and Exhibit 2004
DOI: 10.2514/6.2004-1060
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Mesh Resolution Requirements for Accurate Sonic Boom Prediction of Complete Aircraft Configurations

Abstract: In this paper we conduct a careful study to assess the numerical mesh resolution requirements for the accurate computation of sonic boom ground signatures produced by complete aircraft configurations. The details of the ground signature can be highly dependent on the accurate prediction of the pressure distribution in the near-field of the aircraft. For this purpose it is necessary to describe the geometric detail of the configuration including the wing, fuselage, nacelles, diverters, etc. and to accurately ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Our previous work in high-fidelity supersonic design had focused on the cruise condition alone. 3,[15][16][17] Although recently we had included some basic constraints to handle other points in the mission, 15 these were only surrogates for the real constraints that must be imposed for realistic designs to be produced. A major component of this work is the addition of PASS to formally include all of the necessary constraints.…”
Section: The Program For Aircraft Synthesis Studiesmentioning
confidence: 99%
“…Our previous work in high-fidelity supersonic design had focused on the cruise condition alone. 3,[15][16][17] Although recently we had included some basic constraints to handle other points in the mission, 15 these were only surrogates for the real constraints that must be imposed for realistic designs to be produced. A major component of this work is the addition of PASS to formally include all of the necessary constraints.…”
Section: The Program For Aircraft Synthesis Studiesmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15] This type of solution adaptive process is often referred to as feature-based adaptation because it focuses on the strong features that are present in the flow solution (e.g., shocks and boundary layers). However, the manual specification and feature-based adaptation methods miss the connection between the impact of local errors on global output quantities (i.e., lift and drag) because these local errors can be transported through the solution to degrade the accuracy of the calculation.…”
Section: Introductionmentioning
confidence: 99%
“…Solution adaptive methods have been shown to accurately and efficiently predict the near-field pressure disturbance. 15,[30][31][32][33] The current adjoint-based error estimation and adaption procedure is applied to to the 3-D Mach 1.26 inviscid flow over two tandem cones connected by a cylinder and a wind tunnel sting. This is a case taken from a 1965 NASA Langley Research Center experiment and analysis reported in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Each individual component module is explained in detail in the following subsections. However in this study, the ground boom signature is not used as an objective function and, therefore, the full solution-adaptive procedure we have used in the past [9,29] to obtain high-quality near-field pressures was not necessary. This greatly simplifies the calculations used to generate multi-fidelity response surfaces.…”
Section: Aerodynamic Analysismentioning
confidence: 99%